2022
DOI: 10.1093/nop/npac061
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in inpatient clinical presentation, treatment, and outcomes in brain metastasis

Abstract: Background Few studies have assessed the impact of race on short-term patient outcomes in the brain metastasis population. The goal of this study is to evaluate the association of race with inpatient clinical presentation, treatment, in-hospital complications, and in-hospital mortality rates for patients with brain metastases (BM). Method Using data collected from the National Inpatient Sample (NIS) between 2004 and 2014, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…For example, prior investigations have shown that factors such as a history of substance use are more likely to cause Black kidney transplant candidates to be denied waitlisting compared with White candidates. The disparate application of these subjective criteria to the detriment of the candidacy of racially minoritized patients is an example of structural racism and is consistent with data from a broad range of health care scenarios demonstrating that implicit practitioner bias has detrimental impacts on the management and outcomes of minoritized patients …”
Section: Discussionsupporting
confidence: 66%
“…For example, prior investigations have shown that factors such as a history of substance use are more likely to cause Black kidney transplant candidates to be denied waitlisting compared with White candidates. The disparate application of these subjective criteria to the detriment of the candidacy of racially minoritized patients is an example of structural racism and is consistent with data from a broad range of health care scenarios demonstrating that implicit practitioner bias has detrimental impacts on the management and outcomes of minoritized patients …”
Section: Discussionsupporting
confidence: 66%
“…races. 6,[8][9][10][11] Other studies investigating racial differences in brain tumor survival have found a survival advantage in Black patients with brain tumors. [12][13][14][15] Because of the considerable variability in treatment recommendations for patients with metastatic brain lesions, it is imperative to understand how prognosis and survival may vary in different populations to ensure equitable care for vulnerable populations and reduce the overall financial burden on the healthcare system.…”
mentioning
confidence: 99%